PEMANFAATAN MELINJO MENJADI OLAHAN EMPING KRIUK DALAM MENINGKATKAN PEREKONOMIAN - Muharnita Muharnita; Haidir Lubis (Bajang Institute, 2023)
The purpose of this research is to establish a melinjo-based business and also to create a source of income amidst unstable economic conditions. A business for crackers made from melinjo was established on Jalan Garu 2, Harjosari I Village, Medan Amplas District. This location was chosen because it is a strategic location, apart from being densely populated there are also 2 universities in it. In establishing a cracker chips business, researchers used a SWOT analysis. The promotion methods used are personal selling and internet marketing. The results of this study, namely the chip cracker business can achieve a profit of up to Rp. 17,850,000/month assuming all the crispy chip products produced per day (50 pcs) are sold out.